Long Non-coding RNA Aerrie Controls DNA Damage Repair via YBX1 to Maintain Endothelial Cell Function - Pham, Tan Phát; Bink, Diewertje I.; Stanicek, Laura; van Bergen, Anke; van Leeuwen, Esmee; Tran, Yvonne; Matic, Ljubica; Hedin, Ulf; Wittig, Ilka; Dimmeler, Stefanie; Boon, Reinier A. (Frontiers in Cell and Developmental Biology, 2021)
Aging is accompanied by many physiological changes. These changes can progressively lead to many types of cardiovascular diseases. During this process blood vessels lose their ability to maintain vascular homeostasis, ultimately resulting in hypertension, stroke, or myocardial infarction. Increase in DNA damage is one of the hallmarks of aging and can be repaired by the DNA signaling and repair system. In our study we show that long non-coding RNA Aerrie (linc01013) contributes to the DNA signaling and repair mechanism. Silencing of Aerrie in endothelial cells impairs angiogenesis, migration, and barrier function. Aerrie associates with YBX1 and together they act as important factors in DNA damage signaling and repair. This study identifies Aerrie as a novel factor in genomic stability and as a binding partner of YBX1 in responding to DNA damage.